Multi-temporal analysis between 1975 and 2015 on changes in glacier coverage in the snowy Allin Capac and Chichi Capac, Peru - Díaz Aguilar, Renny Daniel (2017)
The objective of the study was the multi-temporal analysis between 1975 and 2015, on changes in glacier coverage in the snowy Allin Capac and Chichi Capac, Peru. The area covered by glaciers was estimated using the supervised classification method for Landsat 2 image and the normalized difference snow index for Landsat 5 and Landsat 8 images. The results of the analysis show a drastic decrease of the glacier cover in the snowy Allin Capac and Chichi Capac. Thus, in 1975 the area of ​​glacier coverage was 52.3 km2 and by 2015 was reduced to 16.9 km2, losing a total of 35.6 km2. In 1975, the 35% of the glacier coverage was below the 5000 m.a.s.l. and by the 2015 it represents only 9% of the total glacier area. The greatest setback is evident in the last three decades of the 20th century, with a smaller decline during the first two decades of the 21th century. It is concluded that in the last 40 years, the glacier cover of the snowy Allin Capac and Chichi Capac shows a reduction of 67%, equivalent to a decrease of 17% per decade and an average rate of 0.89 km2 / year.